PENGGUNAAN PAIR COUNSELING UNTUK MENINGKATKAN KEMAMPUAN PERSPECTIVE TAKING SISWA - Eko Darminto (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This writing proposed conseptual idea about pair-counseling application to increase perspective taking ability. Same researches proved that perspective taking can effect social behavior. Based on that data, perspective taking can be used as intervention target to handle some behavioral disorders such as violence among teenagers. Theoritically, peer counseling has effective therapitic characteristics to upgrade perspective taking. Some techniques in pair counseling and the playing environment can develop perspective taking ability among children and teenagers.